2017
DOI: 10.1002/2017gl073736
|View full text |Cite
|
Sign up to set email alerts
|

Variability in seasonal forecast skill of Northern Hemisphere winters over the twentieth century

Abstract: Seasonal hindcast experiments, using prescribed sea surface temperatures (SSTs), are analyzed for Northern Hemisphere winters from 1900 to 2010. Ensemble mean Pacific/North American index (PNA) skill varies dramatically, dropping toward zero during the mid‐twentieth century, with similar variability in North Atlantic Oscillation (NAO) hindcast skill. The PNA skill closely follows the correlation between the observed PNA index and tropical Pacific SST anomalies. During the mid‐century period the PNA and NAO hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 41 publications
13
59
0
Order By: Relevance
“…15 for moving 31-year windows. The variability in correlation closely follows the variability in PNA skill demonstrated in seasonal hindcast experiments of the PNA by O'Reilly et al (2017). In the mid-century period, the ensemble mean correlation disappears, owing to the weakness in the observed ENSO teleconnection to the North Pacific.…”
Section: Implications For Extratropical North Pacific Predictabilitymentioning
confidence: 68%
See 2 more Smart Citations
“…15 for moving 31-year windows. The variability in correlation closely follows the variability in PNA skill demonstrated in seasonal hindcast experiments of the PNA by O'Reilly et al (2017). In the mid-century period, the ensemble mean correlation disappears, owing to the weakness in the observed ENSO teleconnection to the North Pacific.…”
Section: Implications For Extratropical North Pacific Predictabilitymentioning
confidence: 68%
“…O'Reilly et al (2017) showed that in Northern Hemisphere seasonal hindcast experiments the skill of the PNA varies dramatically over the 20th century, closely following the observed relationship between ENSO and the PNA. The drop in skill over the North Pacific in the mid-20th century also corresponds to a period of reduced skill in over the Euro-Atlantic sector O'Reilly et al 2017). Understanding the nature of the interdecadal variability in the ENSO teleconnection to the North Pacific is therefore crucial in determining how seasonal forecast skill has varied in the past and may possibly change going forwards.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The dashed grey lines depict return level uncertainties calculated from ERA-Interim only NAO phase; however the loss during the negative phase is also lower than for the mean across all years and ensembles. Studies have shown that the NAO in seasonal forecasts can be predicted with significant skill (e.g., Scaife et al, 2014;O'Reilly et al, 2017). As a result, this would mean that a seasonal forecast exhibiting extreme NAO values for a season bears the potential of either above or below average windstorm damage.…”
Section: Estimated Damage Linked With Large-scale Driver Indicesmentioning
confidence: 99%
“…Since the sensitivities were estimated from a control integration of a coupled model and were treated as being constant in time, further improvements of the method could include sensitivities depending on the atmospheric state, for instance, for phases of either low or high NAO states, which have shown to impact the predictability of the NAO (O'Reilly et al, ).…”
Section: Discussionmentioning
confidence: 99%